ANISAH NUR,- (2023) PENGARUH PEMBELAJARAN MANDIRI BERBASIS TEKNOLOGI TERHADAP KEMAMPUAN LITERASI DIGITAL (STUDI PADA LANSIA di KELURAHAN GEGERKALONG KOTA BANDUNG. - Anisah Nur, - (2023)
ABSTRACT Digital literacy is referred to as a set of competencies related to skills in using computers and information technology. Digital literacy is an activity that understands media technology that is formed in sharing basic knowledge with digital media users, including the millennial generation who are proficient in using technology. This study aims to see the effect of self directed learning on digital literacy skills in the elderly in the Gegerkalong Village, Bandung City. This research uses a quantitative approach with descriptive research methods. The population in this study was 4,426 people and the research sample was 97 people. Data collection tools use questionnaires, questionnaires, and Google forms. Data analysis used hypothesis testing using simple linear regression analysis and SPSS Version 26. The results of this study indicated that: 1) The independent learning process was seen as successful in the elderly in Gegerkalong Village, Bandung City. 2) Improving digital literacy skills more effectively. 3) The elderly's perception of the independent learning that is carried out has an influence on the increase in digital literacy skills achieved. Conclusions of this study state that the process of technology-based independent learning on digital literacy skills can be seen from the largest average value found in the male sex and the 50-59 year old age category who carry out digital literacy skills with independent learning show higher ability results. Good. Keywords: Self Directed Learning, Digital Literacy, Community Education.